How artificial intelligence is enhancing innovation in healthcare / Assoc. Prof. Dr. Fazlin Mohd Fauzi - Mohd Fauzi, Fazlin (Faculty of Pharmacy, 2023)
The healthcare industry is constantly evolving, with new advancements and technologies emerging frequently. One of the most promising developments in recent years is the increasing integration of artificial intelligence (AI) in healthcare. AI has the potential to revolutionise healthcare by predicting and preventing disease outbreaks, as well as identifying the most effective treatments for individual patients. With the ability to analyse vast amounts of data, AI algorithms can uncover patterns and relationships that may not be immediately apparent to humans.